Domino Math to Improve Elementary School Students' Understanding of Mathematical Measurement Concepts - Mar’atu Zahra; Rahayu Condro Murti; Firmansyah (Universitas Pendidikan Ganesha, 2025)
Indonesian students' mathematics learning outcomes remain unsatisfactory. Students still experience difficulties understanding basic mathematical concepts, especially in connecting abstract material to everyday life. This study aims to analyze the effectiveness of Domino Math media in improving elementary school students' understanding of measurement concepts through a group-comparison meta-analysis. This study uses a quantitative, meta-analytic approach. Data were collected through the PRISMA method from the Google Scholar database in the period 2015-2025. Of the 500 articles searched, 7 met the inclusion criteria and were analyzed using JASP to calculate effect sizes and levels of heterogeneity. The results showed an effect size of 1.478 (p = 0.009) in the high category, indicating that Domino Math significantly improves understanding of measurement concepts. Although there is high heterogeneity (I² = 91.426%), the effect direction remains consistent. The conclusion of this study is that domino math learning has a positive, significant effect on students' understanding of mathematical concepts in elementary school. This research implies that Domino Math is an effective and innovative medium for improving conceptual understanding while creating a fun learning atmosphere in elementary schools.